A little toleration, please. Issue 6 (1st December 2000) - McKnight, Christopher
Abstract : Value pluralism does not imply relativism or subjectivism about values. What it does is allow respect for an at least limited toleration of values with which one may profoundly disagree. Thus a doctor can respect the autonomy of a patient whose values he does not share.